Pemalsuan Uang di Kota dalam Tinjauan Kriminologi - FIkri Ferdiansyah A. Pakaya; Dian Ekawaty Ismail (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Based on the results of the study, the transaction mode is the most often used mode in the act of circulating and counterfeiting money and economic factors are the main factors for a person to commit the crime of counterfeiting money, as well as efforts made by the police in preventing and exposing the crime of counterfeiting. The transaction mode is the mode most often used by rupiah counterfeiters because this mode is easy to circulate counterfeit money. Economic factors are the most important factor for perpetrators to commit the crime of counterfeiting rupiah. Because the economy is squeezed, someone commits a crime to meet their economic needs. The efforts made by the Gorontalo City Police to prevent the occurrence of rupiah counterfeiting crimes are pursued with three efforts, namely preventive efforts, premative efforts, and repressive efforts. The crime of counterfeiting rupiah is a criminal act in which it contains a system of untruthfulness or falsehood of something (object) that appears from the outside as if it is true, when in fact it is contrary to the real thing that is called the crime of counterfeiting, including currency counterfeiting. The legal basis of money and currency is Law Number. 7 of 2011 concerning Currency, which was promulgated in the Statute Book of the Republic of Indonesia Year 2011 Number. 64 and Supplement to the Statute Book of the Republic of Indonesia No. 5223 This research was conducted to find out the factors and modes of the perpetrators of a criminal act of counterfeiting money in Gorontalo City and to find out the efforts made by the relevant legal parties in an effort to prevent the occurrence of the crime of counterfeiting rupiah money in Gorontalo City.